Formação de professores para a educação inclusiva - Ferlin, Flávia Cristiane [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The present study on teacher training for an effective inclusive education, doing this through works published on the internet. The provocation for carrying out this research came from the following question: What are the teaching difficulties related to teaching for students in the process of inclusion? To answer this question, the general objective is to describe what the bibliographies say in research on teacher training for inclusive education. With this, for the progress of this research, we focus our search on the following specific objectives: identify, from the bibliography, which relative difficulties in teacher training for inclusive education; to analyze how research focuses on teacher training aiming at inclusive education. This is a bibliographical research of a qualitative nature, investigating in reflections of other authors their perception about the formation of the teacher in the face of inclusive education. As support for this the following authors: Silva (2020), Mantoan (2011), Minetto (2010), Mendonça (2015), Carvalho (2014), Piovesan, (2019), Oliveira (2017), Santose Lima (2020), among others, in addition to Brazilian laws that ensure inclusive education. In view of the research carried out, it was possible to perceive that although there are laws that provide assistance to inclusive education and advances in teacher training, it still needs to be reconciled with all aspects that may favor the improvement of the quality of education for children. With special needs, since, later, the formation of this student will reflect on his life in society, in which, this education, must provide him the ability to live independently, however, for this, it is necessary that the school and society transform itself to offer the welcome that these children deserve. It is believed, with this study, that there may be a contribution to the reflections on inclusion, since the relevance of research in the social and academic scope is significant.

O presente estudo sobre a formação docente para uma educação inclusiva efetiva, fazendo isso através de trabalhos publicados na internet. A provocação para a realização dessa pesquisa se deu a partir da seguinte indagação: Em que consistem as dificuldades docentes relativas ao ensino para alunos em processo de inclusão? Para responder tal questão, apresenta-se como objetivo geral: descrever o que dizem as bibliografias em pesquisas sobre a formação docente para a educação inclusiva. Com isso, para o progresso dessa pesquisa, debruçarem nossa busca diante os seguintes objetivos específicos: identificar, a partir das bibliográficas, quais dificuldades relativas na formação docente para a educação inclusiva; analisar como as pesquisas focalizam a formação do professor visando a educação inclusiva. Trata- se de uma pesquisa bibliográfica de cunho qualitativo, investigando em reflexões de outros autores a percepção deles sobre a formação do professor diante a educação inclusiva. Como suporte par tal os seguintes autores: Silva (2020), Mantoan (2011), Minetto (2010), Mendonça (2015), Carvalho (2014), Piovesan, (2019), Oliveira (2017), Santose Lima (2020), entre outros, além das leis brasileiras que asseguram a educação inclusiva. Diante a pesquisa realizada, pôde-se perceber que apesar de haver leis que dê assistência ao ensino inclusivo e os avanços enquanto a formação do professor, ainda necessita da conciliação com todos os aspectos em que possa favorecer para a melhoria na qualidade de ensino para crianças com necessidades especiais, visto que, posteriormente, a formação desse aluno refletirá na sua vida em sociedade, na qual, essa educação, deve lhe proporcionar capacidade de viver de forma independente, no entanto, para tal, é necessário que a escola e a sociedade se transforme para oferecer o acolhimento que essas crianças merecem. Acredita-se, com esse estudo, que possa haver contribuição diante as reflexões sobre a inclusão, visto que a relevância da pesquisa no âmbito social e acadêmico é significativa.
Teacher training for inclusive education
Keywords: Inclusion; School; Teacher training; Inclusão; Escola; Formação de professores